Fighting Misinformation: Benchmarking Education Initiatives in Spain - Verón Lassa, José Juan; Sancho-Ligorred, Belén; Pérez-Zapater, Brenda (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Misinformation is a significant problem affecting society on both individual and collective levels, impacting emotional, psychological, and national security aspects. Due to the lack of a standardized response from educational administrations, civil society initiatives have increased to highlight the issue's severity and equip young people with essential tools. This research identifies, analyzes, and compares recent initiatives in Spain focused on educating children and young people using a qualitative case analysis methodology. The study emphasizes the need for innovative, compulsory, and transversal educational initiatives from an early age, addressing the uncoordinated responses of public and private institutions.